Transfusion reactions associated with COVID‐19 convalescent plasma therapy for SARS‐CoV‐2 - Nguyen, Freddy T.; Akker, Tayler; Lally, Kimberly; Lam, Hansen; Lenskaya, Volha; Liu, Sean T. H.; Bouvier, Nicole M.; Aberg, Judith A.; Rodriguez, Denise; Krammer, Florian; Strauss, Donna; Shaz, Beth H.; et al. (Transfusion (Philadelphia, Pa.), 2021)
Background Convalescent plasma (CP) for treatment of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has shown preliminary signs of effectiveness in moderate to severely ill patients in reducing mortality. While studies have demonstrated a low risk of serious adverse events, the comprehensive incidence and nature of the spectrum of transfusion reactions to CP is unknown. We retrospectively examined 427 adult inpatient CP transfusions to determine incidence and types of reactions, as well as clinical parameters and risk factors associated with transfusion reactions. Study Design and Methods Retrospective analysis was performed for 427 transfusions to 215 adult patients with coronavirus 2019 (COVID‐19) within the Mount Sinai Health System, through the US Food and Drug Administration emergency investigational new drug and the Mayo Clinic Expanded Access Protocol to Convalescent Plasma approval pathways. Transfusions were blindly evaluated by two reviewers and adjudicated by a third reviewer in discordant cases. Patient demographics and clinical and laboratory parameters were compared and analyzed. Results Fifty‐five reactions from 427 transfusions were identified (12.9% incidence), and 13 were attributed to transfusion (3.1% incidence). Reactions were classified as underlying COVID‐19 (76%), febrile nonhemolytic (10.9%), transfusion‐associated circulatory overload (9.1%), and allergic (1.8%) and hypotensive (1.8%) reactions. Statistical analysis identified increased transfusion reaction risk for ABO blood group B or Sequential Organ Failure Assessment scores of 12 to 13, and decreased risk within the age group of 80 to 89 years. Conclusion Our findings support the use of CP as a safe, therapeutic option from a transfusion reaction perspective, in the setting of COVID‐19. Further studies are needed to confirm the clinical significance of ABO group B, age, and predisposing disease severity in the incidence of transfusion reaction events.